Value and capital management : a handbook for the finance and risk functions of financial institutions - Wilson, Thomas C., 1961- (Hoboken : Wiley, 2015)
"A value management framework designed specifically for banking and insurance The Value Management Handbook is a comprehensive, practical reference written specifically for bank and insurance valuation and value management. Spelling out how the finance and risk functions add value in their respective spheres, this book presents a framework for measuring - and more importantly, influencing - the value of the firm from the position of the CFO and CRO. Case studies illustrating value-enhancing initiatives are designed to help Heads of Strategy offer CEOs concrete ideas toward creating more value, and discussion of "hard" and "soft" skills put CFOs and CROs in a position to better influence strategy and operations. The challenge of financial services valuation is addressed in terms of the roles of risk and capital, and business-specific "value trees" demonstrate the source of successful value enhancement initiatives. While most value management resources fail to adequately address the unique role of risk and capital in banks, insurance, and asset management, this book fills the gap by providing concrete, business-specific information that connects management actions and value creation, helping readers to: Measure value accurately for more productive value-based management initiatives and evaluation of growth opportunities Apply a quantitative, risk-adjusted value management framework reconciled with the way financial services shares are valued by the market Develop a value set specific to the industry to inspire initiatives that increase the firm's value Study the quantitative and qualitative management frameworks that move CFOs and CROs from measurement to management The roles of CFO and CRO in financial firms have changed dramatically over the past decade, requiring business savvy and the ability to challenge the CEO. The Value Management Handbook provides the expert guidance that leads CFOs and CROs toward better information, better insight, and better decisions"--
Machine generated contents note: List of Abbreviations Preface Acknowledgments About the Author Part I: Introduction Chapter 1: Why is Value Management Important? Chapter 2: How do CFOs and CROs Add Value? Part II: Better Information -- Measuring Value Chapter 3: RAPM -- The Industry Standard Chapter 4: Two Challenges in Using RAPMs Chapter 5: Valuing Financial Services -- The Theory Chapter 6: Valuing Financial Services -- The Evidence Chapter 7: Market Consistent Valuation for Insurers Part III: Better Insights -- Managing Value Chapter 8: Property and Casualty Insurance Chapter 9: Life and Health Insurance Chapter 10: Banking Chapter 11: Achieving Profitable Growth Chapter 12: Achieving Operating Efficiency Part IV: Better Decisions -- Capital, Balance Sheet and Risk Management Chapter 13: Corporate Strategy and Capital Allocation Chapter 14: Strategic Planning and Performance Management Chapter 15: Balance Sheet Management Chapter 16: Economics of Asset / Liability Management Chapter 17: The Practical Aspects of Asset / Liability Management Chapter 18: Cash and Liquidity Management Chapter 19: Managing the Capital and Funding Structure Chapter 20: Risk Management Chapter 21: Risk Governance and Organization Chapter 22: Risk Identification and Evaluation Chapter 23: Risk Underwriting -- Strategy and Governance Chapter 24: Risk Underwriting -- Technical Tools Chapter 25: Risk Underwriting -- From Technical Pricing to Value Maximization Chapter 26: Managing Operational and Reputational Risks Chapter 27: Risk and Limit Controlling Appendix Glossary Bibliography Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Banks and banking; Financial services industry; Risk management; BUSINESS & ECONOMICS -- Finance; Banks and banking; Financial services industry; Risk management; Electronic books